Pi of the Sky observation of GRB160625B - Opiela, R.; Batsch, T.; Castro-Tirado, A.; Czyrkowski, H.; Cwiek, A.; Cwiok, M.; Dabrowski, R.; Jelinek, M.; Kasprowicz, G.; Majcher, A.; MaLek, K.; Mankiewicz, L.; et al. (2017)
© 2017 SPIE. Pi of the Sky is a system of wide field of view robotic telescopes, which search for short timescale astrophysical phenomena, especially for prompt optical GRB emission. The system was designed for autonomous operation, monitoring a large fraction of the sky to a depth of 12 m '13 m and with time resolution of the order of 10 seconds. Custom designed CCD cameras are equipped with Canon lenses f = 85 mm, f/d = 1.2 and cover 20° × 20° of the sky each. The final system with 16 cameras on 4 equatorial mounts was completed in 2014 at the INTA El Arenosillo Test Centre in Spain. GRB160625B was an extremely bright GRB with three distinct emission episodes. Cameras of the Pi of the Sky observatory in Spain were not observing the position of the GRB160625B prior to the first emission episode. Observations started only after receiving Fermi/GBM trigger, about 140 seconds prior to the second emission. As the position estimate taken from the Fermi alert and used to position the telescope was not very accurate, the actual position of the burst happened to be in the overlap region of t wo cameras, resulting in two independent sets of measurements. Light curves from both cameras were reconstructed using the Luiza framework. No object brighter than 12.4 m (3s limit) was observed prior to the second GRB emission. An optical flash was identified on an image starting -5.9s before the time of the Fermi/LAT trigger, brightening to about 8m on the next image and then becoming gradually dimmer, fading below our sensitivity after about 400s. Emission features as measured in different spectral bands indicate that the three emission episodes of GRB160625B were dominated by distinct physics process. Simultaneously observations in gamma-rays and optical wavelengths support the hypothesis that this was the first observed transition from thermal to non-thermal radiation in a single GRB. Main results of the combined analysis are presented.